ANALISIS KEADAAN USAHA BUDIDAYA IKAN SISTEM KERAMBA JARING APUNG ( KJA) DI DANAU TOBA ( KASUS DESA UNTEMUNGKUR KECAMATAN MUARA KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA) - Sitompul, Fadly; Ramli, M.; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACT This study was conducted on May 7 to 15, 2014, aims to determine how much investment and operational costs and problems faced by farmers in the cultivation of fish in floating net cages in the village Untemungkur. The method used in this research is to conduct interviews respondents were 9 people divided into Category I and Category II From the research that has been conducted in the village of Muara Untemungkur on farming in floating net cages in mind that a large total investment of fish farming in floating net cages for category I Rp.161.935.000, with operating expenses of Rp.81.641.568, / harvest. Net income is farming Rp38.358.432, / harvest. As for category II total investment fish farming in floating net cage aquaculture transform Rp.130.905.000 category II, namely, - the operating expenses of Rp.61.701.778, - / harvest. The advantages are achieved net farmers in this village is supported by the ability of farmers in the supplementary feeding. Keyword : Village Untemungkur , investment , Business Advantage (π)